The Rising Food Prices in Ramadan and Its Impact on Inflation - Mutiara, Tira; Al Arif, Mohammad Nur Rianto; Anwar, Muhammad (Faculty of Economic and Business, Universitas Islam Negeri Syarif Hidayatullah, 2025)
Research Originality: This study proposes a new contribution by analyzing the seasonal pattern of rising food prices in Ramadan and its impact on inflation over the period 2018–2024. This data range allows for more recent and relevant identification. Research Objectives: This study aims to describe food prices before, during, and after Ramadan and to analyze their impact on inflation, using data from January 2018 to May 2024. Research Methods: This research uses descriptive statistical methods to analyze food prices and inflation, and multiple linear regression to examine the impact of food prices on inflation. Empirical Results: This study found that prices of all food commodities tended to increase before, during, and after Ramadan, especially in Ramadan 2022. Descriptively, inflation also showed an increasing pattern before, during, and after Ramadan in most observation years, except 2020. Multiple linear regression analysis revealed that only chicken prices had a significant effect on inflation, while the other nine foods did not. Implications: These findings suggest that the government prioritize controlling the prices of strategic commodities like chicken during Ramadan by stabilizing supply and disseminating price information equitably. Furthermore, education on wise consumption and support for food access for poor groups can help mitigate price fluctuations on the demand side. JEL Classification: Q110, E310, E210 How to Cite:Mutiara, T., Al Arif, M. N. R., & Anwar, M. (2025). The Rising Food Prices in Ramadhan and Its Impact on Inflation. Signifikan: Jurnal Ilmu Ekonomi, 14(2), 407-422. https://doi.org/10.15408/sjie.v14i2.46417.